Salinadaptatus halalkaliphilus gen. nov., sp. nov., a haloalkaliphilic archaeon isolated from salt pond in Inner Mongolia Autonomous Region, China. Issue 1 (4th January 2021) - Xue, Qiong; Zuo, Zhenqiang; Zhou, Heng; Zhou, Jian; Zhang, Shengjie; Han, Jing; Zhao, Dahe; Xiang, Hua
Abstract : A haloalkaliphilic strain XQ-INN 246 T was isolated from the sediment of a salt pond in Inner Mongolia Autonomous Region, China. Cells of the strain were rods, motile and strictly aerobic. The strain was able to grow in the presence of 2.6–5.3 M NaCl (optimum concentration is 4.4 M) at 30–50 °C (optimum temperature is 42 °C) and pH 7.0–10.0 (optimum pH is 8.0–8.5). The whole genome sequencing of strain XQ-INN 246 T revealed a genome size of 4.52 Mbp and a DNA G+C content of 62.06 mol%. Phylogenetic tree based on 16S rRNA gene sequences and concatenated amino acid sequences of 122 single-copy conserved proteins revealed a robust lineage of the strain XQ-INN 246 T with members of related genera of the family Natrialbaceae . The strain possessed the polar lipids of phosphatidylglycerol and phosphatidylglycerol phosphate methyl ester. No glycolipids were detected. Based on phylogenetic analysis, phenotypic characteristics, chemotaxonomic properties and genome relatedness, the isolate was proposed as the type strain of a novel species of a new genus within the family Natrialbaceae, for which the name Salinadaptatus halalkaliphilus gen. nov., sp. nov. is proposed. The type strain is XQ-INN 246 T (=CGMCC 1.16692 T =JCM 33751 T ).